Penggunaan Inkuiri Terbimbing untuk Meningkatkan Keterampilan Sains Siswa di Sekolah Menengah Pertama - Helsy Elselia (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Science process skills are needed by students when learning science so that students can carry out a series of activities as scientists do. This study aims to improve students' ability to formulate problems and hypothesize through guided inquiry learning. This research was conducted using a quantitative method through the mechanism of pre-test and post-test in each learning cycle with a different concept in the odd semester of class VIII Junior Hight School 2 Tanjungsari. The concepts taken in this study are Plant Growth and Development, Respiratory System, and Plant Tissue Functions. There was an increase in cognitive ability from the results of the test and the skills in writing problem formulations and students' hypotheses in that there was an increase in the range of numbers that were not too far away in each cycle. The editorial problem formulation and students' hypotheses showed that there was a relationship between the variables in the study. Student learning participation in groups is getting better, especially when collecting data and discussing data analysis.